Antioxidant and prooxidant activities of tea polyphenols in oil-in-water emulsions depend on the level used and the location of proteins. (1st May 2022) - Tian, Li; Zhang, Shulin; Yi, Jianhua; Zhu, Zhenbao; Cui, Leqi; Andrew Decker, Eric; Julian McClements, David
Highlights: Tea polyphenols (TP) were incorporated into emulsions containing proteins. TP acted as antioxidants toward lipids and non-absorbed proteins. But TP acted as pro-oxidants or antioxidants for adsorbed proteins depending on dose. The location of proteins in emulsions affected the pro-/anti-oxidative activity of TP. Abstract: We studied the impacts of protein location (interface or aqueous phase) on the antioxidant and prooxidant activities of tea polyphenols (TP) in model oil-in-water emulsions (pH 7) at a low (0.01% w/v) or high (0.04 % w/v) concentration. TP at 0.01% reduced the levels of both lipid and protein oxidation markers in emulsions, independent of the protein location. However, TP were more potent when proteins were located at the interface. At 0.04%, TP were only weakly antioxidant towards lipids but were prooxidant towards proteins in emulsions with proteins at the interface, whereas they were still somewhat antioxidant for aqueous phase proteins. These results indicate that TP may act as either antioxidants or prooxidants depending on their concentration and also on the location of the proteins in emulsions. The level of TP should be optimized for emulsion-based foods or beverages to achieve optimum antioxidant activity.